Linha de base cumulativa e sistema de conseqüências no ensino informatizado de leitura - Cordioli, Raquel Baccarin Ribeiro (2009)
The study evaluated two versions of a computerized program for teaching reading skills (de Souza e de Rose, 2006) which was intended to teach the relations between sets of stimuli consisting of a written word, a picture and a spoken word. Although developed to ensure that the apprentice advance at his own pace, the steps of this program were designed to teach fixed sets of three words. This meant that until he reaches the criterion of 100% of hits for the whole set, the participant keeps repeating the same step. This feature may require a number of unnecessary steps, and also result in damage to the motivation, as the participant can judge he is not progressing. The objective of this study was to determine whether a new organization of the steps of teaching, including only words whose relations are not mastered by the participant, could expedite the conclusion of the program. Additionally, it embedded a virtual album of stickers with the function of providing feedback to the learner of his performance. The stickers were presented as a consequence to the establishment of relations between the stimuli of each of the sets. In Study I the new procedure was introduced to five participants who were being exposed to the original persion and the results showed an acceleration in the pace of learning for four of the five participants. In Study II, the assessment of reading is held throughout the cumulative baseline and not only for last 15 words of the unit, as determined in previous procedures. The program was completed when the participant completed the reading of 60 words. Eleven students with different entry repertoires in reading completed the Study II. The data were compared to 14 students with similar repertoire that had completed the original version. The new version resulted in a decrease in the total number of sessions for most participants. A more pronounced decrease was observed in achieving the first half of the expected repertoire in this study. Another result observed was greater number of words taught by the intermediary sessions. The new contingencies of teaching led to a higher individual progress, greater variability in the content taught and can accelerate the progress of the participant.